If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (16y + 4x) + -1(6x + 10y) = 0 Reorder the terms: (4x + 16y) + -1(6x + 10y) = 0 Remove parenthesis around (4x + 16y) 4x + 16y + -1(6x + 10y) = 0 4x + 16y + (6x * -1 + 10y * -1) = 0 4x + 16y + (-6x + -10y) = 0 Reorder the terms: 4x + -6x + 16y + -10y = 0 Combine like terms: 4x + -6x = -2x -2x + 16y + -10y = 0 Combine like terms: 16y + -10y = 6y -2x + 6y = 0 Solving -2x + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. -2x + 6y + -6y = 0 + -6y Combine like terms: 6y + -6y = 0 -2x + 0 = 0 + -6y -2x = 0 + -6y Remove the zero: -2x = -6y Divide each side by '-2'. x = 3y Simplifying x = 3y
| t-8+3t=12 | | -24+21y=20 | | -3m=15 | | 3x+19=6x+34 | | 64p^3q-25pq^3= | | 3(6-y)=6 | | 1x+2=26 | | -9=4-n/2 | | (d-3)(d+5)=-12 | | 3y+17=47 | | .18(y-5)+.16=0.02-0.03(70) | | 2(w+4)=12 | | 2.5y=(y+5) | | 7.8(h-1)=6h+4+2h | | 5-y=3y+7 | | n/5=185 | | m+2/5=2m-3/8 | | 8(2x-5)=2(8x+1) | | x^2+10x-20=1 | | -1+13+11x+12x=24 | | -6z+6=-10-8z | | 9x+7=97 | | 4+7x=3x-20 | | y^2+2y-7y-14= | | 5x+4=9-2x | | 6p=3p-9 | | x-7y=-8 | | x-7y= | | (2-8x)-(x+4)= | | 8+16x-2=9x+90-5x | | M-5=155.3 | | 12b^3-11b^2+2b=0 |